The Role of Good Corporate Governance and Financial Performance on The Disclosure of Corporate Social Responsibility - Putri Estiarto , Lintang; Hariadi, Bambang (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to examine the effect of Good Corporate Governance (GCG) and financial performance on the disclosure of Corporate Social Responsibility (CSR). This study was devoted to mining companies listed on the Indonesia Stock Exchange (IDX) during 2018 - 2019. GCG is measured by four proxies, namely the proportion of directors, the proportion of independent commissioners, and the independence of the audit committee. Meanwhile, to see the financial performance, this study uses the Return on Equity (ROE) Ratio. The extent of CSR disclosure is measured by the method of analyzing the content of the company's annual report related to CSR activities and the amount issued by the company for its CSR activities. The final sample of this study was 73 observations. To test the hypothesis, multiple linear regression analysis was used. The results of this study will later prove that the proportion of Directors, Independent Commissioners, Audit Committee Independence, and financial performance will increase the positive effect on CSR disclosure. Meanwhile, the Independent Board of Commissioners is not proven to have an effect on CSR disclosure. Abstrak Penelitian ini bertujuan untuk menguji pengaruh Good Corporate Governance (GCG) dan kinerja keuangan terhadap pengungkapan Corporate Social Responsibility (CSR). Penelitian ini dikhususkan pada perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) selama tahun 2018 – 2019. GCG diukur dengan empat proksi yaitu proporsi direksi, proporsi komisaris independen, dan independensi komite audit. Sedangkan untuk melihat kinerja keuangan, penelitian ini menggunakan Rasio Return on Equity (ROE). Luasnya pengungkapan CSR diukur dengan metode analisis isi laporan tahunan perusahaan yang berkaitan dengan kegiatan CSR dan jumlah yang dikeluarkan perusahaan untuk kegiatan CSR-nya. Sampel akhir penelitian ini sebanyak 73 observasi. Untuk menguji hipotesis digunakan analisis regresi linier berganda. Hasil penelitian ini nantinya akan membuktikan bahwa proporsi Direksi, Komisaris Independen, Independensi Komite Audit, dan kinerja keuangan akan meningkatkan pengaruh positif terhadap pengungkapan CSR. Sedangkan